PELATIHAN PEMBUATAN SIRUP BUAH NIPAH SEBAGAI PRODUK UNGGULAN DESA SEMPAN KABUPATEN BANGKA - Nurhadini, Nurhadini; Fabiani, Verry Andre; Asriza, Ristika Oktavia; Puspita Sari, Fajar Indah (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Sempan Village is one of the villages in Pemali District of Bangka Regency, Bangka Belitung Islands which do not yet have the featured products, while this village has nipah plants that are not used optimally. The nipah fruit can be further processed into a featured product of village i.e. syrup. The service program Chemistry Department is training Sempan Village society on the manufacture of syrup from nipah fruit. The method of this activity includes three stages i.e. preparation, implementation and evaluation. After this activity is carried out, the Sempan Village society have increased understanding, knowledge and motivation in utilizing nipah fruit into processed syrup products and this product is expected become one of the featured products of Sempan VillageKeywords: nipah fruit, syrup, Sempan Village